FEATURES OF COMBINING THE RESULTS OF 3D LASER SCANNING FROM DIFFERENT STATIONS USING MAGNETIC SPHERES - Batrakova, A.; Hunko, I.; Dorozhko, Ye.; Sarkisian, H.; Urdzik, S. (Municipal economy of cities (Technical science), 2024)
3D laser scanning is becoming an increasingly important technology in the modern world, opening up endless possibilities for obtaining accurate geometric parameters of various objects. So, due to its efficiency and accuracy, this technology is becoming indispensable in such industries as surveying, construction support, executive surveying, geodetic monitoring, and others. However, despite the many advantages of laser scanning, it has a limitation that can significantly affect the results, namely the algorithm for stitching individual scans into a single-point cloud. Most scanners do not have built-in capabilities to stitch together scan results from multiple stations automatically. Therefore, obtaining a single-point cloud requires using alternative methods. Modern laser scanner companies offer a variety of models with unique technical characteristics. The right choice of scanner functionality is crucial when performing various technological tasks throughout the entire process, from scanning to obtaining the result. The technical parameters of laser scanners, such as measurement accuracy, maximum scanning range, and scanning speed, vary depending on the type of objects scanned and the necessary results. The use of magnetic spheres becomes an essential aspect of ensuring scanning accuracy. They facilitate stitching data from different stations and allow automated search for stitching points, simplifying data processing. An algorithm built into Trimble RealWorks software automatically detects magnetic spheres in the point cloud. It uses an appropriate transformation to join two adjacent scans from different stations if more than three identical spheres are present. The article aims to study the peculiarities of combining the results of 3D laser scanning from several stations using magnetic spheres. It discusses the analysis of the technical parameters of the Trimble TX6 laser scanner, variations in the use of magnetic spheres to ensure the accuracy of combining scanning results, and the advantages and disadvantages of this approach.